ANALYSIS OF WORK ENVIRONMENT AT BLOW MOULDING STATION USING 5S METHOD AND FISHBONE DIAGRAM - Panjaitan, Nismah; Yuman, Syafiq Alhadi (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2023)
A good work environment will increase job satisfaction, morale, and employee performance. The company has 5 production stations, namely Printing and Can Making, Blow Moulding, Shortening and Margarine, Filling, and the last is Finished Product Store. Based on observations at the Printing and Can Making, Blow Moulding, Shortening and Margarine, Filling, and Finished Product Store stations, there are unclean and untidy conditions at the Blow Moulding station. Fishbone diagrams are also used to determine the root causes of work environment problems. The cause of the Blow Moulding station being unclean and untidy is the human factor and the method applied. Based on the problems obtained the 5S method is used to arrangement and maintenance of the workplace which was developed through intensive efforts in the work environment of the blow moulding station. When everything has its place and there is the right position, then the 5S program will serve to provide a clear picture of a good workplace.